The reflective teacher education: teaching as an object of research - Altair Alberto Fávero; Carina Tonieto; Marisa Fátima Roman (Universidade Federal de Santa Maria, 2013)
The continuing education of teachers has become a compulsory subject in our time. There is a consensus among teachers and school leaders regarding the need to "educate the educators", because the rational knowledge learned in the process of formation of teachers is not sufficient to face the complexity and the diversity of the problems that the teachers' work demands. It is necessary and urgent, in any area from education, to reflect about the new forms of exercising the skills needed for the professional practice. In regards to teaching, reflecting in and about the practice enables the educator to reconsider their own performance. The focus of this essay is to analyze the continuing education of teachers from the paradigm of the reflective teacher. KEYWORDS: Reflective teacher, Formative process, Educational policies.